Analisis Analisis Pengaruh Iklan Media Sosial terhadap Keputusan Pembelian di E-Commerce: PENDAHULUAN - Ega Pratama; M Raka Perdiana; Kelvin Yudistira; Farrel Hansah; Faisal Abror; M Ripaldi; Destiarini Destiarini (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid growth of social media has transformed digital marketing strategies in e-commerce platforms. Social media advertising has become one of the most widely used tools by companies to attract consumers and influence purchasing decisions. This study aims to analyze the effect of social media advertising on consumer purchasing decisions in e-commerce platforms. The research applied a quantitative approach by collecting data through questionnaires distributed to active e-commerce users who frequently use social media. The collected data were analyzed using descriptive statistical methods and simple linear regression analysis. The findings indicate that social media advertising has a positive and significant influence on consumer purchasing decisions. More attractive, informative, and interactive advertisements tend to increase consumers’ interest in purchasing products through e-commerce platforms. This study is expected to provide useful insights for business actors in developing more effective digital marketing strategies through social media advertising.